Fabrication of sustainable magnesium phosphate cement micromortar using design of experiments statistical modelling: Valorization of ceramic-stone-porcelain containing waste as filler. Issue 8 (15th April 2021) - Huete-Hernández, S.; Maldonado-Alameda, A.; Giro-Paloma, J.; Chimenos, J.M.; Formosa, J.
Abstract: Magnesium phosphate cement (MPC) is a potential sustainable alternative to Portland cement. It is possible to lower the total CO2 emissions related to MPC manufacturing by using by-products and wastes as raw materials. When by-products are used to develop MPC, the resultant binder can be referred to as sustainable magnesium phosphate cement (sust-MPC). This research incorporates ceramic, stone, and porcelain waste (CSP) as a filler in sust-MPC to obtain a micromortar. Sust-MPC is formulated with KH2 PO4 and low-grade MgO (LG-MgO), a by-product composed of 40–60 wt% MgO. CSP is the non-recyclable glass fraction generated by the glass recycling industry. The effect of water and CSP addition on the mechanical properties of sust-MPC was analyzed using design of experiments (DoE). A statistical model was obtained and validated by testing ideally formulated samples achieved through optimization of the DoE. The optimal formulation (15 wt% of CSP and a water to cement ratio of 0.34) was realized by maximizing the compressive strength at 7 and 28 days of curing, resulting in values of 18 and 25 MPa respectively. After one year of curing, the micromortar was physico-chemically characterized in-depth using backscattered scanning electron microscopy (BSEM-EDS) and Fourier transform infrared-attenuated total reflectance spectroscopy (FTIR-ATR). The optimal formulation showed good integration of CSP particles in the ceramic matrix. Thus, a potential reaction between silica and the K-struvite matrix may have occurred after one year of curing.